Management Of Coffee-Based Gastronomy Tourism In Twenty Milli And Secondfloor Coffee Bali - Neneng Sri Mulyati; Putu Sucita Yanthy, Putu Sucita Yanthy; Yohanes Kristianto, Yohanes Kristianto (International Journal of Economics, Business and Innovation Research, 2025)
Coffee-based gastronomic tourism has become a distinctive tourist attraction that combines culinary, cultural, and experiential elements. In Bali, Twenty Milli Coffee Roastery and Secondfloor Coffee represent leading examples of this tourism model. This research explores the activities and management strategies implemented by both cafés and evaluates their contributions to enhancing Bali’s tourism appeal. Using a mixed-methods approach, data were collected through observations, interviews, documentation, and questionnaires. Qualitative data were analyzed using NVivo software for thematic coding, while quantitative data were processed using Likert scale and Importance Performance Analysis (IPA). The results indicate that both cafés deliver high-quality tourism experiences, fulfilling visitor expectations in key areas such as attraction, amenities, accessibility, motivation (push and pull), and consumer behavior. Twenty Milli and Secondfloor Coffee successfully manage core resources, human, financial, technological, material, and market to build engaging and sustainable experiences. Although their approaches differ, both emphasize synergy between internal and external business environments. NVivo analysis reveals that educational experiences, storytelling, and customer involvement are central to creating authenticity and uniqueness in coffee tourism. This research highlights that success in this field is driven not only by product quality but also by innovation in service, experience design, and consumer education. It is recommended that other coffee businesses adopt similar strategies, while government stakeholders should provide regulatory and promotional support to strengthen the growth of coffee-based gastronomic tourism.